STATUS KEBERLANJUTANPENGELOLAAN TERUMBU KARANG DI PULAU HOGOW DAN PUTUS-PUTUS SULAWESI UTARA - Rembet, Unstain NWJ; Boer, Mennofatria; Bengen, Dietriech G; Fahrudin, Achmad (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2011)
ABSTRACTA study aimed to examine the status of sustainable management of coral reef in Pulau Hogow and Pulau Putus-Putus in Southeast Minahasa regency, North Sulawesi Province, was conducted in from July to September 2011. Diagnosis on the status of sustainable management of coral reef was presented in a sequence covering the ecological, economic, social, institutional and technological dimensions. In ecological dimension, the attribute of percentage of coral cover provided the largest contribution. In economical dimension, the largest contribution was provided by tourism guide, time used for coral reefs exploitation, dependency on the resource as a source of income and foreign tourists attributes. In social dimension, similar indications shown by the attributes of the number of locations which were potential for exploitation conflicts, level of education and efforts to repair the damage of coral reef ecosystems. On the institutional dimension, the contributions made by all attributes were almost even, with the highest is the tradition/culture and cooperation attributes. Similarly, in the technological dimension the contributions made attributes were almost even, with the highest contributions were from boat technology and technology post-harvest technology attributes. For overall dimensions of sustainability management of coral reefs, a map created in RAPFISH ordinate showed recommendation on the status of the sustainability.Keywords: sustainability, management, coral reef, dimension.ABSTRAKPenelitian ini bertujuan untuk menelaah status keberlanjutan pengelolaan te-rumbu karang di Pulau Hogow dan Putus-Putus Kabupaten Minahasa Tenggara Provinsi Sulawesi Utara, dilakukan pada bulan Juli-September 2011. Diagnosis status keberlanjutan pengelolaan terumbu karang dikemukakan secara berurutan mencakup dimensi ekologi, dimensi ekonomi, dimensi sosial, dimensi kelembagaan dan dimensi teknologi. Dalam dimensi ekologi atribut persentase penutupan karang memberikan kontribusi terbesar. Untuk dimensi ekonomi kontribusi terbesar diberikan atribut pe-mandu wisata, waktu yang digunakan untuk pemanfaatan terumbu karang, ketergan-tungan kepada sumberdaya sebagai sumber nafkah dan wisatawan mancanegara. Di-mensi sosial indikasi serupa ditunjukkan oleh atribut-atribut jumlah lokasi potensi kon-flik pemanfaatan, tingkat pendidikan dan upaya perbaikan kerusakan ekosistem terum-bu karang. Pada dimensi kelembagaan kontribusi yang diberikan atribut-atribut merata, tetapi yang tertinggi adalah tradisi/budaya dan koperasi. Demikian juga pada dimensi teknologi, kontribusi yang diberikan atribut-atribut merata, dengan kontribusi tertinggi adalah atribut teknologi perahu dan teknologi pasca panen. Untuk semua dimensi keberlanjutan pengelolaan terumbu karang, hasil pemetaan yang dilakukan dalam ordinasi RAPFISH menunjukkan status keberlanjutan yang baik untuk dilakukan.Kata kunci: keberlanjutan, pengelolaan, terumbu karang, dimensi.